Thoroughbreds - Taylor-Joy, Anya, 1996-; Cooke, Olivia, 1993-; Yelchin, Anton (Universal Pictures Home Entertainment, 2018)
Two upper-class teenage girls in suburban Connecticut rekindle their unlikely friendship after years of growing apart. Together, they hatch a plan to solve both of their problems-no matter what the cost.
Childhood friends Lily (Anya Taylor-Joy) and Amanda (Olivia Cooke) reconnect in suburban Connecticut after years of growing apart. Lily is now a polished, upper-class teenager at a fancy boarding school; Amanda has turned into a sharp-witted outcast with an attitude. Though they seem at odds, the pair bonds over Lily's contempt for her oppressive stepfather, and they begin to bring out one another's most destructive tendencies. Their ambitions lead them to hire a local hustler and take matters into their own hands to set their lives straight.
Originally released as a motion picture in 2017
Director, Cory Finley.
Anya Taylor-Joy, Olivia Cooke, Anton Yelchin.
MPAA rating: R.
DVD.
English audio.